Understanding the barriers of culturally relevant, responsive, and equity-centered teaching in STEM higher education: Faculty insights from the literature - Osuji, Uche; Mason, Rihana (American Journal of STEM Education, 2026)
Our review examined the literature on faculty perceptions related to implementing CRP in STEM higher education. Following PRISMA guidelines, we synthesized studies from multiple disciplines to identify the trends in faculty perspectives on barriers to adopting CRP. The findings revealed: 1) limited understanding and practical constraints in applying CRP, and 2) resistance to CRP from students, colleagues, and institutional structures, as the broad classifications of the challenges faculty face with CRP. We also discussed the implications for overcoming the barriers. The implications highlight the need for comprehensive professional development, institutional support, and a shift in disciplinary norms to foster inclusive and equitable STEM education. This work provides insights into creating more culturally responsive learning environments in STEM higher education.